Diet preference of the different life stages of the aquatic grasshopper Cornops aquaticum (Orthoptera: Acrididae) and its implications for the biológica! control of water hyacinth - Franceschini, María Celeste (2022)
Fil: Franceschini, María Celeste. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.